NOVEL SELF-MICROEMULSIFYING DRUG DELIVERY SYSTEM FOR ENHANCED DIABETES MANAGEMENT: EVALUATING THE COMBINED EFFECTS OF GLIMEPIRIDE AND BOSWELLIA SERRATA EXTRACT (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
This study aimed to create and assess a novel self-microemulsifying drug delivery system (SMEDDS) for treating diabetes mellitus that contains glimepiride and Boswellia serrata extract. In the creation of SMEDDS formulations, Transcutol-P was employed as the base oil, while the surfactants Tween 80 and propylene glycol/polyethylene glycol 400 served as the co-surfactants. To improve the formulation, pseudoternary phase diagrams were created. While the SMEDDS of B. serrata extract showed a mean droplet size of 27.63 nm, 98.3% transmittance, a zeta potential of -0.11 mV, and a polydispersity index of 0.287, the glimepiride-optimized SMEDDS showed a mean droplet size of 14.8 nm, 98.5% transmittance, a zeta potential of -0.10 mV. In-vivo evaluation on diabetes-induced rats demonstrated significant reductions in SGOT and SGPT levels with the glimepiride and B. serrata extract SMEDDS compared to diabetic control rats and the marketed glimepiride formulation. The formulation showed promising results in controlling serum total protein, triglyceride, and cholesterol levels. The glimepiride and B. serrata extract SMEDDS also exhibited antioxidant activity, reducing malondialdehyde (MDA) absorbance. Histopathological assessment of kidney and pancreas tissues revealed the protective effects of the concomitant administration of glimepiride and B. serrata extract SMEDDS formulation against diabetes-induced damage. Overall, the developed SMEDDS formulation kit showed superior in-vitro and in-vivo performance, suggesting its potential as an effective therapeutic option for managing diabetes mellitus.